High-technology entrepreneurship in Silicon Valley - Robert W. Fairlie; Aaron K. Chatterji (University of California, Economics Department, 2011)
The economic expansion of the late 1990s created many opportunities for business creation in Silicon Valley, but the opportunity cost of starting a business was also high during this period because of the exceptionally tight labor market. A new measure of entrepreneurship derived from matching files from the Current Population Survey (CPS) is used to provide the first test of the hypothesis that business creation rates were high in Silicon Valley during the Roaring 90s. Unlike previous measures of firm births based on large, nationally representative datasets, the new measure captures business creation at the individual-owner level, includes both employer and non-employer business starts, and focuses on only hi-tech industries. Estimates indicate that hi-tech entrepreneurship rates were lower in Silicon Valley than the rest of the United States during the period from January 1996 to February 2000. Examining the post-boom period, we find that entrepreneurship rates in Silicon Valley increased from the late 1990s to the early 2000s. Although Silicon Valley may be an entrepreneurial location overall, we provide the first evidence that the extremely tight labor market of the late 1990s, especially in hi-tech industries, may have suppressed business creation during this period.
Keywords: 330; Entrepreneurship; High-technology; Silicon Valley; Economic Geography; Regional Clusters; Hochtechnologiesektor; Unternehmer; Unternehmensgründung; Räumliche Verteilung; Wirtschaftsgeographie; Clusteranalyse; Silicon Valley; USA